Analysis of Integrated Marketing Communication (IMC) Strategy in Increasing Market Share: Case Study of Selingkar Yogyakarta - Sri Utami; Azizah, Nurul (PT Inovasi Pratama Internasional, 2023)
This research aims to provide valuable guidance for marketing practitioners and product developers in developing appropriate and effective IMC strategies. So this research can encourage increased awareness, acceptance and adoption of literacy education products in Selingkar. In this research, descriptive qualitative data collection techniques were used, as well as the data collection process through observation, interviews and documentation. The source of this research is the founder of Selingkar and marketing officer of Selingkar. The research results show that Selingkar has implemented an integrated IMC strategy, including advertising, direct marketing, sales promotion, personal sales, sponsorship, word of mouth, public relations and social media marketing which have an impact on market share . However, the application of IMC is still limited to technology. Additionally, this integration helps manage marketing budgets more effectively and allows for more accurate measurement of campaign results.